Concomitant t(8;21) and trisomy 4 in a patient with Acute Myeloid Leukemia (AML) - Phan CL,; Ong TC,; Chang KM,; Zubaidah Z,; Puteri Jamilatul NMB, (Penerbit UKM, 2010)
The t(8;21)(q22;q22) is a frequently occurring aberration in acute myeloid leukemia (AML) (18-20%) and usually correlate with French-America-British (FAB) M2 subtype. Several studies showed that patients carrying this abnormality demonstrated good response to standard chemotherapy but also have a high incidence of disease relapse. Trisomy 4 is a rare and specific chromosomal abnormality occurring in AML M2 or M4 of the FAB subtypes. We report a case of a 33-year-old female with an apparently clinical and hematologic diagnosis of acute promyelocytic leukemia (APL) in whom cytogenetic analysis revealed an abnormal karyotype with trisomy 4, in addition to t(8;21). Trisomy 4 and t(8;21) in a patient with AML is rare. The significance of t(8;21) with trisomy 4 in AML are unclear but patients bearing this abnormality are associated with a poor prognosis.